2013
DOI: 10.1128/jvi.02885-12
|View full text |Cite
|
Sign up to set email alerts
|

Tropism and Infectivity of Influenza Virus, Including Highly Pathogenic Avian H5N1 Virus, in Ferret Tracheal Differentiated Primary Epithelial Cell Cultures

Abstract: Tropism and adaptation of influenza viruses to new hosts is partly dependent on the distribution of the sialic acid (SA) receptors to which the viral hemagglutinin (HA) binds. Ferrets have been established as a valuable in vivo model of influenza virus pathogenesis and transmission because of similarities to humans in the distribution of HA receptors and in clinical signs of infection. In this study, we developed a ferret tracheal differentiated primary epithelial cell culture model that consisted of a layered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 48 publications
(92 reference statements)
6
54
0
Order By: Relevance
“…3) is in agreement with the findings of a prior study showing enhanced H5N1 virus attachment to feline type II pneumocytes in the lower respiratory tract but not to tracheal tissue (54). Thus, the reduced infectivity of NY/108 virus but not NY/107 virus in cultures of FTECs (which possess a greater density of ␣2-6-linked than ␣2-3-linked SA [31]) and the reduced transmissibility of NY/108 virus compared with that of NY/107 virus among ferrets (18) suggest that differences between the HAs of these two LPAI H7N2 viruses may be present. One potential change may be an Ala135Ser substitution in NY/108 virus HA that predicts a 4th N-glycosylation site at position 133, which is not present in NY/107 virus, Tky/VA virus, or the great majority of sequenced North American avian viruses.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3) is in agreement with the findings of a prior study showing enhanced H5N1 virus attachment to feline type II pneumocytes in the lower respiratory tract but not to tracheal tissue (54). Thus, the reduced infectivity of NY/108 virus but not NY/107 virus in cultures of FTECs (which possess a greater density of ␣2-6-linked than ␣2-3-linked SA [31]) and the reduced transmissibility of NY/108 virus compared with that of NY/107 virus among ferrets (18) suggest that differences between the HAs of these two LPAI H7N2 viruses may be present. One potential change may be an Ala135Ser substitution in NY/108 virus HA that predicts a 4th N-glycosylation site at position 133, which is not present in NY/107 virus, Tky/VA virus, or the great majority of sequenced North American avian viruses.…”
Section: Discussionsupporting
confidence: 82%
“…Cells of the human bronchial epithelial cell line Calu-3 (ATCC) were grown on 12-well membrane inserts and cultured as previously described (28). Ferret differentiated primary tracheal epithelial cells (FTECs) were isolated and cultured as previously described (31). Calu-3 cells were cultured under submerged conditions, and ferret primary cells were cultured under air-liquid interface (ALI) conditions.…”
Section: Virusesmentioning
confidence: 99%
“…3a, b; 4a, b). We confirmed the observations of Zeng et al (2013), that the ciliated cell type in FTE cultures abundantly expressed a2,6 SA, and showed that these cells were the targets of influenza B/Florida/04/2006 (Yamagata lineage) virus infection. Recent reports have described lineage specific SA binding preferences (the Yamagata-like lineage displaying a a2,6 linkage preference and the Victoria-like viruses an a2,6 and a2,3 binding affinity) (Wang et al, 2012).…”
Section: Huang Et Al (2014) Recently Compared the Replication Of Fousupporting
confidence: 77%
“…Death of airway epithelial cells due to viral replication, excessive inflammation and/or loss of repair functions can damage the integrity of the airway epithelium (Herold et al, 2008;Hinshaw et al, 1994;Kash et al, 2011;Schultz-Cherry et al, 2001;Zeng et al, 2013). One consequence of this compromised natural barrier can be invasive bacterial infection.…”
Section: Compromising the Epithelial Barrier Functionmentioning
confidence: 99%